Analyzing the distribution patterns and dynamic niche of Magnolia grandiflora L. in the United States and China in response to climate change - Zhang, Wenqian; Wang, Xinshuai; Shen, Shouyun; Zhao, Yanghui; Hao, Siwen; Jiang, Jinghuan; Zhang, Donglin (Frontiers in Plant Science, 2024)
Magnolia grandiflora L. (southern magnolia) is native to the southeastern coastal areas of the United States of America, from North Carolina to the east end of Texas (USDA Cold Hardiness Zone 8). It is presently widely cultivated in Zone 5-10 in US and the south Yangtze River in China. A few studies have been focused on how climate change and human activities had affected the geographical distribution patterns and the range of introductions of M. grandiflora and assessed its adaptability to new environments and its distribution during its introduction to China. We selected 127 occurrence points in the USA and 87 occurrence points in China and 43 environmental variables to predict the suitable habitat areas for M. grandiflora in the USA and China using present climate data and projected future climate data under the complete niche based on the ensemble model (EM) Biomod2 package. Then, we predicted the niche change of M. grandiflora in USA and China employing the 'ecospat' package in R. Our results identified the EM models achieved high reliability and strong reference value with an AUC of 0.993 and TSS of 0.932. Solar radiation in July, human impact index, and precipitation of wettest month were identified as the most critical variables for shaping M. grandiflora distribution. M. grandiflora exhibits a similar trend of distributional extension in both countries under the climate change scenarios, with expansion to the northwest and northeast and contraction to the south to varying degrees. Our study emphasized a practical framework for suitable habitats and migration of Magnoliaceae species under climate change scenarios, which will guide species conservation, plant introduction, management strategies, and sustainable utilization.